ANALISIS DINAMIKA KEPEMIMPINAN TUNANETRA DENGAN METODE INTERPRETATIF (STUDI KASUS DI IKATAN TUNANETRA MUSLIM INDONESIA JAKARTA SELATAN) - Akbar, Rafik; Gani, Nur Asni (Taksasila Edukasi Insani, 2025)
This study aims to analyze the leadership dynamics of blind individuals within the Muslim Blind Association of Indonesia (ITMI) South Jakarta using an interpretative case study approach. The research focuses on the implementation of the organization’s statutes (ADART) in leadership processes, the role of members in leadership selection, and the strategic contribution of the Regional Syuro Council as a guardian of organizational values and direction. The findings indicate that although ADART provides a strong normative framework, member comprehension of its content and principles remains limited. Member participation is also varied, influenced by access to information, personal networks, and a lack of systematic cadre education. The Syuro Council plays a significant role in candidate verification and strategic recommendation, albeit consultative in nature. The study concludes that leadership dynamics within ITMI South Jakarta result from interactions between formal structures, Islamic values, and the collective culture of the blind community. Strengthening organizational literacy, reforming participation mechanisms, and adapting to technological advancements are necessary to enhance inclusive and democratic organizational governance. Keywords: Blind Leadership, Organizational Statutes, Member Participation, Syuro Council, Disability Organization